WEB SISTEM INFORMASI BERBASIS W2000 UNTUK DUKUNGAN PEMESANAN DAN PENJUALAN PRODUK SAFETY - Frieyadie, Frieyadie (Jurnal Pilar Nusa Mandiri, 2014)
The problem faced by the marketing officer, in a conventional system in which the data collection order for the goods still using paper media carbonates quadruplicate and still handwritten by marketing staff. Documenting ordering goods still using paper media carbonates quadruplicate and still handwritten by marketing staff. Relatively frequent errors in the writing of the carbon and impenetrable in because the writing is less pressured and miscalculations because of misreading the code of goods. Data collection on the availability of goods in the form of name document stock less open. Documenting the availability of goods using Microsoft Excel. The purpose of this study so that sales order (SO) data is not handwritten anymore, but via online order monitoring by employees who are out of the office. Methods of analysis using qualitative methods, and methods W2000, used as an approach for web development information systems